2015
DOI: 10.1016/j.rboe.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the AO/ASIF and Gartland classifications for supracondylar fractures of the humerus in children

Abstract: ObjectiveTo evaluate the reproducibility of the radiographic classifications of Gartland and the Association for Osteosynthesis/Association for the Study of Internal Fixation (AO/ASIF) for supracondylar fractures of the humerus in children.MethodsOn two occasions, 50 radiographs in anteroposterior and lateral views were evaluated by three pediatric orthopedists in accordance with the Gartland and AO/ASIF pediatric classifications. Their responses were subjected to statistical analysis consisting of calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…A more recent study from Brazil between three paediatric orthopaedic surgeons found substantial interobserver agreement overall, excellent interobserver agreement for type I fractures, moderate interobserver agreement for type II fractures, substantial interobserver agreement for type III fractures and excellent intraobserver agreement overall. 8 Finally, a study by Leung et al 9 between five USA-based surgeons found moderate interobserver agreement overall and substantial intraobserver agreement overall. They questioned the utility of the Wilkins-modified classification system in guiding clinical decision-making, particularly for type II fractures where the reliability of classification between surgeons is low.…”
Section: Discussionmentioning
confidence: 94%
“…A more recent study from Brazil between three paediatric orthopaedic surgeons found substantial interobserver agreement overall, excellent interobserver agreement for type I fractures, moderate interobserver agreement for type II fractures, substantial interobserver agreement for type III fractures and excellent intraobserver agreement overall. 8 Finally, a study by Leung et al 9 between five USA-based surgeons found moderate interobserver agreement overall and substantial intraobserver agreement overall. They questioned the utility of the Wilkins-modified classification system in guiding clinical decision-making, particularly for type II fractures where the reliability of classification between surgeons is low.…”
Section: Discussionmentioning
confidence: 94%
“…In children Supracondylar fracture of the humerus is the most common fracture around the elbow [9]. Type I (Gartland) fractures can be adequately managed by immobilization in an above elbow cast [10]. However, controversy exists regarding the optimal treatment for displaced supracondylar fracture (Gartland type II & type III).…”
Section: Discussionmentioning
confidence: 99%
“…The Gartland classification system categorizes SHF into 3 categories based on severity of displacement. Specifically, type I SHF is not displaced; type II is angulated with the posterior cortex intact; type III is completely displaced with no cortical contact [6,7]. Bone displacement in Gartland type III SHF is difficult to correct by manipulative reduction as the realigned fractured ends have minimal contact and poor stability, making splint and plaster external fixation extremely difficult.…”
Section: Discussionmentioning
confidence: 99%